Review of Trine Stauning Willert’s, New Voices in Greek Orthodox Thought: Untying the Bond between Nation and Religion - Markoviti, Margarita (Historein, 2017)
Trine Stauning Willert. New Voices in Greek Orthodox Thought: Untying the Bond between Nation and Religion. Burlington: Ashgate, 2014. viii + 197 pp